A Constructive Heuristic Algorithm for Distribution System Planning - Lavorato, Marina; Rider, Marcos J.; Garcia, Ariovaldo V.; Romero, Ruben [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2010)
A constructive heuristic algorithm (CHA) to solve distribution system planning (DSP) problem is presented. The DSP is a very complex mixed binary nonlinear programming problem. A CHA is aimed at obtaining an excellent quality solution for the DSP problem. However, a local improvement phase and a branching technique were implemented in the CHA to improve its solution. In each step of the CHA, a sensitivity index is used to add a circuit or a substation to the distribution system. This sensitivity index is obtained by solving the DSP problem considering the numbers of circuits and substations to be added as continuous variables (relaxed problem). The relaxed problem is a large and complex nonlinear programming and was solved through an efficient nonlinear optimization solver. Results of two tests systems and one real distribution system are presented in this paper in order to show the ability of the proposed algorithm.
Keywords: AMPL; constructive heuristic algorithm; distribution system planning; KNITRO; mixed binary nonlinear programming; power systems optimization